ANALISIS MULTIDISIPLINER SOCIAL-POLITIK MADRASAH DI INDONESIA - Rusmaeni; Iyayun Amalia; Wahyu Mulyadin; Ilham; Andy Abdillah Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the socio-political dynamics that shape the development of madrasahs in Indonesia through a multidisciplinary approach integrating sociology, political science, and public policy. The central problem of this research lies in the limited understanding of how social structures, cultural identities, and state policies collectively influence the governance, quality, and transformation of madrasahs in the contemporary era. The study aims to explain the social foundations of madrasah identity, examine political and policy factors affecting institutional management, and explore the modernization processes occurring within madrasah education amid global changes. Using a qualitative descriptive method supported by literature studies, document analysis, and thematic interpretation, this research identifies three major findings: (1) madrasahs function as cultural and social institutions rooted in community identity and religious values; (2) political dynamics, bureaucratic structures, and budget distribution significantly determine the operational effectiveness of madrasahs; and (3) modernization efforts including curriculum reform, digital integration, and capacity building position madrasahs as adaptive institutions capable of responding to global educational demands. The study concludes that the development of madrasahs in Indonesia is a complex interplay of social forces and political structures, requiring collaborative governance and continuous innovation to enhance competitiveness and strengthen their role within the national education system.